2014
DOI: 10.1590/s1516-635x2014000100014
|View full text |Cite
|
Sign up to set email alerts
|

Effects of glycerol on the metabolism of broilers fed increasing glycerine levels

Abstract: This study evaluated the metabolic response of broilers fed diets containing increasing crude glycerine levels in two bioassays. Birds were house in metabolic cages, and were distributed according to a completely randomized experimental design with five treatments of 4 replicates each (1 st assay: 5 birds/ cage; 2 nd assay: 1-20 days = 8 birds/ cage, and 21-42 days = 4 birds/cage). Treatments consisted of a control diet based on corn and soybean meal, and four other diets containing 2.5%, 5.0%, 7.5% and 10.0% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 13 publications
1
20
1
4
Order By: Relevance
“…Gianfelici (2009) and Romano et al (2014) observed that levels higher than 7.5% of glycerin in broiler diets increased water consumption and excretion, which may have adverse effects on the field due to higher litter moisture. Glycerin is a low molecular weight hydrophilic compound, which is easily excreted by the kidneys.…”
Section: Evaluation Of Dietary Glycerin Inclusion During Different Brmentioning
confidence: 99%
“…Gianfelici (2009) and Romano et al (2014) observed that levels higher than 7.5% of glycerin in broiler diets increased water consumption and excretion, which may have adverse effects on the field due to higher litter moisture. Glycerin is a low molecular weight hydrophilic compound, which is easily excreted by the kidneys.…”
Section: Evaluation Of Dietary Glycerin Inclusion During Different Brmentioning
confidence: 99%
“…It was found that raw glycerine could be efficiently utilized when included at levels up to 10% in the starter diet phase. Romano et al (2014) observed a linear interaction between glycerine levels and bird age on daily feed intake. Bernardino et al (2015) studied the influence of pure and semi-pure glycerine addition with varying levels (0, 17.5, 35, 52.5 and 70 g · kg ) on broiler performance.…”
Section: Introductionmentioning
confidence: 86%
“…Although there are many studies showed positive results of the glycerin as an energy supplement for athlete animals and humans on hot days (Schott et al, 2001;Kavouras et al, 2006;Dozier et al, 2008;Patlar et al, 2012;Romano et al, 2014), there are no studies on the effects of glycerin inclusion in the drinking water of broilers submitted to heat stress. Therefore, the objective of this study was to evaluate the supplementation of pure glycerin the drinking water on the performance of broilers submitted to feed restriction and to cyclic heat stress.…”
Section: Introductionmentioning
confidence: 99%